Fresno County Bar Association's Annual Judges' Dinner at Bob Crossland's Barn - Watkins, Howard::::::::: (1982)
Don Oren, Charles Oren, Barbara St. Louis, Justice Donald Franson, Sr.. Judge Robert Barnard